(untitled) (Journal of the College of Basic Education, 2022)
Palestine will remain the biggest wound in the contemporary history of the Arabs, and since the early second half of the twentieth century, in particular, its divergent repercussions have contributed to directing many civilized changes, which have affected effectively, and sometimes harshly, the development of modern Arab societies, and the challenges they faced. Its political and historical repercussions had a central role in ripening its direct or indirect factors, based on the fact that the Palestine issue, in the Arab collective memory, has civilizational, political, historical, social and cultural dimensions, and therefore it contributed effectively to the creation of hotbeds of transformation, varying effect